Bonded neodymium iron boron magnet

By optimizing material combination and process processing, bonded NdFeB magnets with high magnetic properties and mechanical strength are prepared, which solves the problems of existing magnets being hard, brittle and easy to break, and has poor corrosion resistance. They are suitable for applications in complex environments and reduce production costs.

CN119852047APending Publication Date: 2025-04-18XIANGCI MAGNETIC IND (SHENZHEN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510016437.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing bonded NdFeB magnets are hard and brittle and easy to break, and have poor corrosion resistance and magnetic stability, which limit their application in complex environments.

Method used

By optimizing the material combination, the bonded NdFeB magnets are made of NdFeB magnetic powder, nanoparticles, ceramic additive materials, polymer binders and additive additives. The specific composition is 65%-80% NdFeB magnetic powder, 5%-10% nanoparticles, 10%-15% ceramic additive materials, 5%-20% polymer binders, and 1%-5% additive additives. The magnet improves its mechanical strength and corrosion resistance through low temperature curing and nanocoated surface treatment.

Benefits of technology

It improves the magnetic properties and mechanical strength of bonded NdFeB magnets, enhances its stability and service life in complex environments, and reduces production costs, making it suitable for large-scale production and the manufacturing of complex-shaped magnets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852047A_ABST
    Figure CN119852047A_ABST
Patent Text Reader

Abstract

The invention discloses a bonded neodymium-iron-boron magnet which comprises a bonded neodymium-iron-boron magnet body, and the bonded neodymium-iron-boron magnet body is prepared from the following components in percentage by weight: 65-80% of neodymium-iron-boron magnetic powder, 5-20% of nanoparticles, 5-20% of a ceramic additive material, 5-20% of a polymer binder and 5-20% of an additive aid. 5% to 10% of nano particles; 10%-15% of a ceramic additive material; 5%-20% of a polymer binder; 1%-5% of an additive. According to the bonded neodymium-iron-boron magnet provided by the invention, by optimizing the material combination of the bonded neodymium-iron-boron magnet, the bonded neodymium-iron-boron magnet has relatively high magnetic performance and relatively good mechanical strength, so that the bonded neodymium-iron-boron magnet can be suitable for complex environment occasions requiring both magnetism and strength; therefore, the service life of the bonded neodymium-iron-boron magnet during use is prolonged, the stability of the magnetic performance of the bonded neodymium-iron-boron magnet is improved, and the corrosion resistance and the oxidation resistance of the bonded neodymium-iron-boron magnet are improved through the nano coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of NdFeB magnets, and in particular to a bonded NdFeB magnet. Background Art

[0002] At the end of the 20th century, humans invented NdFeB permanent magnets, using abundant and cheap neodymium to replace rare and expensive cobalt to manufacture rare earth permanent magnets, which not only greatly improved the magnetic properties, but also greatly reduced the dependence on strategic resources - cobalt. Due to the significant reduction in costs, it has become possible to mass-produce and widely use rare earth permanent magnets. NdFeB permanent magnets have higher remanence, coercive force, magnetic energy product, and good dynamic recovery. They are the strongest magnetic materials found in the world. Their magnetic properties are several to dozens of times greater than those of widely used ferrite permanent magnets, and are nearly twice as high as the first and second generation rare earth magnets (Samarium Cobalt permanent magnets). Due to its high performance-price ratio, it is becoming an ideal material for manufacturing high-performance, small-volume, and light-weight magnetic functional devices, and has gradually replaced the position of traditional permanent magnets in various industries.

[0003] Traditional NdFeB magnets often rely on sintering processes, but sintered NdFeB magnets often cannot meet the needs when the shape is complex, the size is small, or a specific magnetic field direction is required. Therefore, bonded NdFeB magnets are used as an alternative because they can be cured at low temperatures and have high molding freedom.

[0004] However, the existing bonded NdFeB magnets are hard and brittle, which makes them easy to break, and their corrosion resistance and magnetic stability are poor, which limits the application of NdFeB magnets in complex environments. Therefore, it is urgent to design a bonded NdFeB magnet to solve the above problems. Summary of the invention

[0005] The object of the present invention is to provide a bonded NdFeB magnet to solve the above-mentioned deficiencies in the prior art.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] A bonded NdFeB magnet comprises a bonded NdFeB magnet, wherein the bonded NdFeB magnet is made of NdFeB magnetic powder, nanoparticles, ceramic additives, a polymer binder and additive additives, and is composed of the following components in weight percentage:

[0008] NdFeB magnetic powder: 65%-80%;

[0009] Nanoparticles: 5%-10%;

[0010] Ceramic additives: 10%-15%;

[0011] Polymer binder: 5%-20%;

[0012] Add additives: 1%-5%.

[0013] Preferably, the NdFeB magnetic powder is composed of neodymium, iron and boron, the mass ratio of neodymium, iron and boron is Nd:Fe:B=30:60:10, the NdFeB magnetic powder is micron-grade powder, and the average particle size of the NdFeB magnetic powder is 1μm-50μm.

[0014] Preferably, the nanoparticles are copolymers formed by combining one or more of ferrite nanoparticles or rare earth metal nanoparticles. The nanoparticles are used to improve the energy density and coercive force of the magnet. The average particle size of the ferrite nanoparticles is 1 nm-10 nm.

[0015] Preferably, the ceramic additive material is a copolymer formed by combining one or more of aluminum oxide and zirconium oxide, and the ceramic additive material is used to improve the heat resistance and mechanical strength of the magnet.

[0016] Preferably, the polymer binder is a copolymer formed by combining one or more of polyimide, epoxy resin, polylactic acid, polyurethane and fluoride.

[0017] Preferably, the additives include toughening agents, antioxidants and plasticizers, and the additives are used to improve the temperature resistance, durability and adaptability of the material.

[0018] Preferably, a method for manufacturing the bonded NdFeB magnet is also provided, comprising the following steps:

[0019] S1: Select high-purity NdFeB magnetic powder, nanoparticles and ceramic additives as raw materials, mix the NdFeB magnetic powder, nanoparticles and ceramic additives in a certain proportion, and then obtain a preliminary mixture;

[0020] S2: putting the mixed preliminary mixture into a ball mill, so that the preliminary mixture can be mixed evenly and have good contact, thereby obtaining a composite material;

[0021] S3: then putting the composite material and the polymer binder into a mixing device, stirring and mixing the composite material and the polymer binder through the mixing device, and then adding an additive during the stirring process, so that the composite material, the polymer binder and the additive are fully mixed to obtain a mixture;

[0022] S4: After obtaining the mixed material, degassing the mixed material after uniform mixing is performed to ensure that bubbles in the mixture are removed;

[0023] S5: placing the mixture into a mold for molding, using compression molding, injection molding or extrusion to form a bonded NdFeB magnet of a desired shape;

[0024] S6: Curing the formed bonded NdFeB magnet at low temperature to ensure that the binder is completely cured and forms a stable structure;

[0025] S7: Surface treatment is performed on the solidified bonded NdFeB magnet to finally obtain a high-performance bonded NdFeB magnet.

[0026] Preferably, the low-temperature curing temperature of the bonded NdFeB magnet in S6 is 80° C.-180° C., and the curing time is 110 h-130 h.

[0027] Preferably, the surface treatment of the bonded NdFeB magnet in S7 is coating an anti-corrosion layer and fine grinding the outer shape, wherein the anti-corrosion layer is used to improve the corrosion resistance of the bonded NdFeB magnet.

[0028] Preferably, the anti-corrosion layer is a nano coating, and the nano coating is one of silicon dioxide and silicon nitride.

[0029] In the above technical solution, the present invention provides a bonded NdFeB magnet, which has the following beneficial effects:

[0030] (1) The bonded NdFeB magnet provided by the present invention optimizes the material combination of the bonded NdFeB magnet so that the bonded NdFeB magnet has relatively high magnetic properties and good mechanical strength, so that the bonded NdFeB magnet can be used in complex environments that require both magnetism and strength, thereby improving the service life of the bonded NdFeB magnet and the stability of its magnetic properties during use.

[0031] (2) The bonded NdFeB magnet provided by the present invention improves the corrosion resistance and oxidation resistance of the bonded NdFeB magnet through a nano-coating, which can ensure the stable operation of the bonded NdFeB magnet in harsh environments, thereby further increasing the service life of the bonded NdFeB magnet during use.

[0032] (3) The bonded NdFeB magnet provided by the present invention has a simple and easy preparation method, is suitable for large-scale production, and can produce magnets of complex shapes to meet different application requirements. It has good economic efficiency, thereby effectively reducing the production and manufacturing costs of the country and enterprises. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can also be obtained based on these drawings.

[0034] Figure 1 A schematic diagram of the structure of a bonded NdFeB magnet embodiment of the present invention.

[0035] Figure 2 A schematic diagram of the manufacturing process structure of a bonded NdFeB magnet embodiment of the present invention.

[0036] Figure 3 A schematic diagram of the bonded NdFeB magnet structure provided for an embodiment of the bonded NdFeB magnet of the present invention. DETAILED DESCRIPTION

[0037] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings.

[0038] like Figure 1-3 As shown, a bonded NdFeB magnet provided by an embodiment of the present invention includes a bonded NdFeB magnet, which is made of NdFeB magnetic powder, nanoparticles, ceramic additives, polymer binders and additives, and consists of the following components in weight percentage:

[0039] NdFeB magnetic powder: 65%-80%; NdFeB magnetic powder is composed of neodymium, iron and boron, the mass ratio of neodymium, iron and boron is Nd:Fe:B=30:60:10, NdFeB magnetic powder is micron-grade powder, and the average particle size of NdFeB magnetic powder is 1μm-50μm;

[0040] Nanoparticles: 5%-10%; the nanoparticles are copolymers composed of one or more of ferrite nanoparticles or rare earth metal nanoparticles. The nanoparticles are used to improve the energy density and coercive force of the magnet. The average particle size of the ferrite nanoparticles is 1nm-10nm;

[0041] Ceramic additives: 10%-15%; Ceramic additives are copolymers made of one or more combinations of alumina and zirconium oxide. Ceramic additives are used to improve the heat resistance and mechanical strength of the magnet;

[0042] Polymer binder: 5%-20%; the polymer binder is a copolymer composed of one or more of polyimide, epoxy resin, polylactic acid, polyurethane and fluoride;

[0043] Additives: 1%-5%; Additives include toughening agents, antioxidants and plasticizers. Additives are used to improve the temperature resistance, durability and adaptability of the material.

[0044] Specifically, in the present embodiment, the NdFeB magnetic powder is made by grinding the NdFeB alloy to ensure its purity; the ferrite nanoparticles have good magnetism and conductivity, which can improve the energy density and stability of the magnet; the rare earth metal nanoparticles use dysprosium or terbium nanoparticles, which can enhance the coercive force of the magnet; the polymer binder can provide certain mechanical strength and corrosion resistance for the bonded NdFeB magnet; the addition of additives can further improve the mechanical strength and corrosion resistance of the bonded NdFeB magnet, and can improve the temperature resistance of the bonded NdFeB magnet.

[0045] The present invention provides a bonded NdFeB magnet, and a method for manufacturing the bonded NdFeB magnet comprises the following steps:

[0046] S1: Select high-purity NdFeB magnetic powder, nanoparticles and ceramic additives as raw materials, mix the NdFeB magnetic powder, nanoparticles and ceramic additives in a certain proportion, and then obtain a preliminary mixture;

[0047] S2: putting the mixed preliminary mixture into a ball mill, so that the preliminary mixture can be mixed evenly and have good contact, thereby obtaining a composite material;

[0048] S3: then putting the composite material and the polymer binder into a mixing device, stirring and mixing the composite material and the polymer binder through the mixing device, and then adding an additive during the stirring process, so that the composite material, the polymer binder and the additive are fully mixed to obtain a mixture;

[0049] S4: After obtaining the mixed material, degassing the mixed material after uniform mixing is performed to ensure that bubbles in the mixture are removed;

[0050] S5: placing the mixture into a mold for molding, using compression molding, injection molding or extrusion to form a bonded NdFeB magnet of a desired shape;

[0051] S6: solidify the formed bonded NdFeB magnet at low temperature to ensure that the binder is completely solidified and forms a stable structure. The low temperature solidification temperature of the bonded NdFeB magnet in S6 is 80℃-180℃, and the solidification time is 110h-130h;

[0052] S7: The surface treatment is performed on the solidified bonded NdFeB magnets to finally obtain high-performance bonded NdFeB magnets. In S7, the surface treatment of the bonded NdFeB magnets is to coat an anti-corrosion layer and finely grind the shape. The anti-corrosion layer is used to improve the corrosion resistance of the bonded NdFeB magnets. The anti-corrosion layer uses a nano coating, which is one of silicon dioxide and silicon nitride.

[0053] In this embodiment, after the solidified bonded NdFeB magnet is surface treated, the NdFeB magnet can also be heat treated, so that the crystal structure of the formed bonded NdFeB magnet can be optimized through heat treatment, thereby further improving the magnetic properties. The heat treatment temperature is 100°C-150°C, and the heat treatment time is 30 minutes-50 minutes.

[0054] Embodiment 1:

[0055] 68% of NdFeB powder with a particle size of 20 microns, 5% of ferrite nanoparticles with a particle size of 5 nanometers, 10% of ceramic additives of alumina and zirconium oxide polymers, 15% of polyimide binders, and 2% of additives are selected. The NdFeB magnetic powder, nanoparticles, ceramic additives, polymer binders, and additives are mixed evenly and degassed. The mixture is placed in a die and formed by a hydraulic press. After forming, it is cured at 150°C for 2 hours. After curing, the magnet is surface treated to obtain a high-performance bonded NdFeB magnet with good corrosion resistance. The remanence of the magnet is tested to be 1.2T and the maximum magnetic energy product is 320kJ / m 3 , the tensile strength is 65MPa, and the coercive force of the magnet at 70°C is greater than 850kA / m.

[0056] Embodiment 2:

[0057] 60% of NdFeB powder with a particle size of 20 microns, 8% of ferrite nanoparticles and rare earth metal nanoparticle copolymers with a particle size of 5 nanometers, 12% of ceramic additives of alumina and zirconia polymers, 15% of epoxy resin binder, and 5% of additives are selected. The NdFeB magnetic powder, nanoparticles, ceramic additives, polymer binder and additives are mixed evenly and degassed. The mixture is placed in a die and formed by a hydraulic press. After forming, it is cured at 150°C for 2 hours. After curing, the magnet is surface treated to obtain a high-performance bonded NdFeB magnet with good corrosion resistance. The remanence of the magnet is tested to be 1.2T and the maximum magnetic energy product is 350kJ / m 3 , the tensile strength is 80MPa, and the coercive force of the magnet at 70°C is greater than 900kA / m.

[0058] Embodiment 3:

[0059] 64% of NdFeB powder with a particle size of 20 microns, 6% of rare earth metal nanoparticles with a particle size of 5 nanometers, 10% of alumina ceramic additives, 16% of polylactic acid binder, and 4% of additives are selected. The NdFeB magnetic powder, nanoparticles, ceramic additives, polymer binder and additives are evenly mixed and degassed. The mixture is placed in a die and formed by a hydraulic press. After forming, it is cured at 150°C for 2 hours. After curing, the magnet is surface treated to obtain a high-performance bonded NdFeB magnet with good corrosion resistance. The remanence of the magnet is tested to be 1.1T and the maximum magnetic energy product is 330kJ / m 3 , the tensile strength is 70MPa, and the coercive force of the magnet at 70°C is greater than 900kA / m.

[0060] The bonded NdFeB magnets prepared by Example 1, Example 2 and Example 3 were tested and the results showed that the bonded NdFeB magnet prepared by Example 2 had the best effect and could effectively meet the working requirements of the bonded NdFeB magnets, showing good magnetic properties, corrosion resistance and mechanical properties, and effectively solving the problem that the existing bonded NdFeB magnet materials are easy to break, and the stability of corrosion resistance and magnetic properties is poor, which limits the application of NdFeB magnets in complex environments.

[0061] The above description is only by way of illustration of certain exemplary embodiments of the present invention. It is undoubted that those skilled in the art can modify the described embodiments in various ways without departing from the spirit and scope of the present invention. Therefore, the above drawings and descriptions are illustrative in nature and should not be construed as limiting the scope of protection of the claims of the present invention.

Claims

1. A bonded NdFeB magnet, characterized in that: The invention comprises a bonded NdFeB magnet, which is made of NdFeB magnetic powder, nanoparticles, ceramic additives, polymer binder and additive additives, and consists of the following components in weight percentage: NdFeB magnetic powder: 65%-80%; Nanoparticles: 5%-10%; Ceramic additives: 10%-15%; Polymer binder: 5%-20%; Add additives: 1%-5%.

2. A bonded NdFeB magnet according to claim 1, characterized in that: The NdFeB magnetic powder is composed of neodymium, iron and boron, the mass ratio of neodymium, iron and boron is Nd:Fe:B=30:60:10, the NdFeB magnetic powder is micron-grade powder, and the average particle size of the NdFeB magnetic powder is 1μm-50μm.

3. A bonded NdFeB magnet according to claim 1, characterized in that: The nanoparticles are copolymers formed by combining one or more of ferrite nanoparticles or rare earth metal nanoparticles. The nanoparticles are used to improve the energy density and coercive force of the magnet. The average particle size of the ferrite nanoparticles is 1nm-10nm.

4. A bonded NdFeB magnet according to claim 1, characterized in that: The ceramic additive material is a copolymer formed by combining one or more of aluminum oxide and zirconium oxide. The ceramic additive material is used to improve the heat resistance and mechanical strength of the magnet.

5. The bonded NdFeB magnet according to claim 1, characterized in that: The polymer binder is a copolymer formed by combining one or more of polyimide, epoxy resin, polylactic acid, polyurethane and fluoride.

6. The bonded NdFeB magnet according to claim 1, characterized in that: The additives include toughening agents, antioxidants and plasticizers, and the additives are used to improve the temperature resistance, durability and adaptability of the material.

7. The bonded NdFeB magnet according to claim 1, characterized in that: The method for making the bonded NdFeB magnet comprises the following steps: S1: Select high-purity NdFeB magnetic powder, nanoparticles and ceramic additives as raw materials, mix the NdFeB magnetic powder, nanoparticles and ceramic additives in a certain proportion, and then obtain a preliminary mixture; S2: putting the mixed preliminary mixture into a ball mill, so that the preliminary mixture can be mixed evenly and have good contact, thereby obtaining a composite material; S3: then putting the composite material and the polymer binder into a mixing device, stirring and mixing the composite material and the polymer binder through the mixing device, and then adding an additive during the stirring process, so that the composite material, the polymer binder and the additive are fully mixed to obtain a mixture; S4: After obtaining the mixed material, degassing the mixed material after uniform mixing is performed to ensure that bubbles in the mixture are removed; S5: placing the mixture into a mold for molding, using compression molding, injection molding or extrusion to form a bonded NdFeB magnet of a desired shape; S6: Curing the formed bonded NdFeB magnet at low temperature to ensure that the binder is completely cured and forms a stable structure; S7: Surface treatment is performed on the solidified bonded NdFeB magnet to finally obtain a high-performance bonded NdFeB magnet.

8. The bonded NdFeB magnet according to claim 7, characterized in that: The low-temperature curing temperature of the bonded NdFeB magnet in S6 is 80° C.-180° C., and the curing time is 110 h-130 h.

9. The bonded NdFeB magnet according to claim 7, characterized in that: The surface treatment of the bonded NdFeB magnet in S7 is coating an anti-corrosion layer and fine grinding the outer shape, wherein the anti-corrosion layer is used to improve the corrosion resistance of the bonded NdFeB magnet.

10. The bonded NdFeB magnet according to claim 9, characterized in that: The anti-corrosion layer adopts a nano coating, and the nano coating is one of silicon dioxide and silicon nitride.